A economia solidária do pensamento utópico ao contexto atual: um estudo sobre experiências em Belo Horizonte - Jonas de Oliveira Bertucci (2005)
The solidarity economics, a recent movement that has emerged in different ways all around the world during the last decades, is frequently seen as a last sigh of the romantic utopian socialism thought. In fact, it is not well defined what would be the so called utopian socialism. On this stigma, different socialist thinkers who have written before Marx and Engels (or either, before the so called scientific socialism) are included. If on the one hand the solidarity economics moves away from the revolutionary radicalism inspired on the Marxist practices, on the other hand it cannot be stigmatized as utopian socialism. It emerges in a new historical context of evolution of the contemporary capitalism and must be understood within this very distinct portrait. The solidarity economics, associating self-management and gift, brings a proposal that has nothing of the rationalism that for Weber would result in the complete disenchantment of the world. Hence, we look to discuss in this dissertation, how the solidarity economics can introduce new elements to the construction of a more democratic and participative society, based on solidarity and with significant differences from the other suggested, studied and practiced forms of socialism until now. We take as an empirical base for the study, a set of experiences developed on the Metropolitan Region of Belo Horizonte. After the theoretical debate we present an ample and general research, accomplished over 84 groups from this region followed by the specific cases of tree solidarity economics cooperatives Coopersoli, Conarte e Courosin. We have attempted to investigate these experiences on political, economical and social aspects.